2015
DOI: 10.1111/nph.13735
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed small RNAs in Arabidopsis galls formed by Meloidogyne javanica: a functional role for miR390 and its TAS3‐derived tasiRNAs

Abstract: SummaryRoot-knot nematodes (RKNs) induce inside the vascular cylinder the giant cells (GCs) embedded in the galls. The distinctive gene repression in early-developing GCs could be facilitated by small RNAs (sRNA) such as miRNAs, and/or epigenetic mechanisms mediated by 24nt-sRNAs, rasiRNAs and 21-22nt-sRNAs. Therefore, the sRNA-population together with the role of the miR390/TAS3/ARFs module were studied during early gall/GC formation.Three sRNA libraries from 3-d-post-inoculation (dpi) galls induced by Meloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
112
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 74 publications
(165 reference statements)
7
112
0
Order By: Relevance
“…More recently, the miR390/TAS3 pathway has been implicated in the interaction of Arabidopsis plants with the parasitic root-knot nematodes. The use of tasiARF sensor and tasiARF-resistant ARF3 lines revealed that this regulatory module is required for nematode-induced gall formation in Arabidopsis roots (Cabrera et al, 2016). In addition, the miR390/TAS3 pathway has been linked to root nodule symbiosis in L. japonicus.…”
mentioning
confidence: 99%
“…More recently, the miR390/TAS3 pathway has been implicated in the interaction of Arabidopsis plants with the parasitic root-knot nematodes. The use of tasiARF sensor and tasiARF-resistant ARF3 lines revealed that this regulatory module is required for nematode-induced gall formation in Arabidopsis roots (Cabrera et al, 2016). In addition, the miR390/TAS3 pathway has been linked to root nodule symbiosis in L. japonicus.…”
mentioning
confidence: 99%
“…In recent years, the role of plant miRNAs in regulation of genes involved in plant-nematode interaction have also been reported [8,16,17]. The most abundant targets of miRNAs that have been reported with modulated expression during nematode infection are transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Zhao and coworkers [20] reported that miR319/TCP4 module acts as a regulator of jasmonic acid levels upon RKN infection in tomato and thereby, affects the nature of host resistance. Recently, functional role of miR390/TAS3 in regulating ARF s at early gall development was studied during Arabidopsis- RKN interaction [17]. In animals, role of miRNAs in relation to diseases have been suggested by predicting the miRNA targets computationally in humans, insects and metazoans [2123].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, J2s from these cultures can be used directly after a simple hatching step in aseptic conditions to infect plants for experiments with different in vitro grown plant species. Successful experiments have been performed with this procedure on different genotypes of Arabidopsis , tobacco, and tomato (Barcala et al, 2010; Escobar et al, 2010; Portillo et al, 2013; Cabrera et al, 2014, 2015, 2016). …”
Section: Introductionmentioning
confidence: 99%